Pemanfaatan Bunga Krisan Bandungan dalam Sediaan “Selly Sante”: Selai Jelly Krisan Stevia - Endang Diyah Ikasari; Endang Dwi Wulansari; Ebta Narasukma Anggraeny; Ungsari Rizki Eka Purwanto; Meysiska Trisnaningtyas; Anggardha Paramita Sutrisno (Politeknik Piksi Ganesha Indonesia, 2025)
Chrysanthemum plants do need enough water, but they can't withstand heavy rain. Several times, bad weather, such as strong winds, causes chrysanthemum farmers to suffer losses because about 90% of chrysanthemums are usually used for event decorations. With the development of food processing technology, chrysanthemums are made into jam with natural sweeteners (Stevia). This encourages our service group to hold counseling and training on chrysanthemum flower processing through the Sido Makmur Farmer Women Group Bandungan. This activity was attended by 20 participants and included product making and counseling about chrysanthemums as antioxidants in jelly food preparations, which can increase the selling value. The service team introduced the method of making natural sweeteners from stevia leaves and used them in the product